Coming of (s)age: religious knowledge, wisdom, and gender in the Hebrew tradition ‘Mishle Sendebar’ - Schmidt, Nora (Das Mittelalter, 2023)
Scriptural intertextuality is a unique hermeneutical strategy of the Hebrew version of the ‘Seven Sages’, the ‘Mishle Sendebar’. This article aims to interpret such strategies of biblical and postbiblical intertextuality and offers an interpretation of selected examples - the encounter of Solomon with the Queen of Sheba in Midrash and retellings of Joseph and Potiphar’s wife - in order to highlight the connectedness of Near Eastern literary and religious traditions of late antiquity and the Middle Ages. By tracing religious knowledge in the frame narrative of the ‘Mishle Sendebar’, the article argues that the Hebrew version of the ‘Seven Wise Masters’ is connected with biblical wisdom discourse, primarily with the book of proverbs and its interpretations. Keywords: Mishle Sendebar; intertextuality; palimpsest; frame narrative; Midrash